156 THE EFFECT OF CARDIOPULMONARY BYPASS TIME AND DONOR ORGAN ISCHEMIC TIME ON THE NEED FOR EXTRACORPOREAL MEMBRANE OXYGENATION AFTER ORTHOTOPIC HEART TRANSPLANTATION IN CHILDREN. Issue 1 (1st January 2007) - Covarrubias, C.; Jocson, R.; Wood, B.; Alejos, J.; Epstein, D.
Abstract : Objective: In children, extracorporeal membrane oxygenation (ECMO) after orthotopic heart transplantation (OHT) poses a significant risk of mortality and morbidity. We hypothesize that prolonged cardiopulmonary bypass (CPB) time and donor organ ischemic time (DOIT) are risk factors for children requiring ECMO immediately following OHT (within 48 hours). Methods: A retrospective chart review of children (≤ 21 years) from a single institution's OHT program between January 1999 and July 2006. Data collected: age, gender, weight, diagnosis, date of OHT, CPB time, DOIT, length of time on ECMO, reason for ECMO, length of hospital and ICU stay, and survival to discharge. Analysis was performed using Fisher's exact test, Student's t -test, and Mann-Whitney U test. Values were considered significantly different for p value < .05. Results: A total of 157 OHTs were reviewed (male = 79; female = 76). Of the total, 142 (90%) received one OHT and 15 (10%) received two OHTs or more. The average age was 10.7 ± 6.5 years (range 0.1-21.5 years). The average weight was 35.3 ± 22.5 kg (range 4-91 kg). Children with heart failure requiring OHT had primary diagnoses of congenital heart disease (26%), transplant coronary artery disease/graft failure (10%), and cardiomyopathy (64%). The average CPB time and DOIT were 142 ± 55 minutes and 229 ± 84 minutes, respectively. There were 11 (7%) children who required ECMO immediately following OHT. The average length of ECMO was 6.1 ± 4.4 days (range 2-14 days). For those requiring ECMO post-OHT and those who did not, the age and weight were not significantly different (9.7 ± 7.2 vs 10.8 ± 6.4 years; p = .60 and 27.3 ± 19.1 vs 35.9 ± 22.7 kg; p = .22, respectively). Upon comparison, children requiring ECMO had a significantly longer CPB time (183 ± 57 vs 139 ± 54 minutes; p = .0067). There was no significant difference of DOIT between those requiring ECMO and those who did not (273 ± 102 vs 225 ± 82 minutes; p = .13). For children requiring ECMO immediately after OHT, their ICU length of stay was significantly longer (35.6 ± 56.4 vs 13.5 ± 18.7 days; p = .015). However, the hospital length of stay (ECMO vs no ECMO) was not significantly different (43.7 ± 57.2 vs 20.7 ± 20.2 days, respectively; p = .28). Patients requiring ECMO immediately post-OHT had a significantly higher mortality (55% vs 2.7%; p < .0001; RR = 2.42, 95% CI = 1.13-5.16). Conclusion: While length of CPB was associated with an increased risk of requiring ECMO immediately post-OHT, DOIT was not. Children requiring ECMO immediately after orthotopic heart transplantation had a significantly longer ICU stay and a higher risk of mortality.